Study on the Properties of High Purity Germanium Crystals. (April 2015) - Yang, G; Mei, H; Guan, Y T; Wang, G J; Mei, D M; Irmscher, K
Abstract: In the crystal growth lab of South Dakota University, we are growing high purity germanium (HPGe) crystals and using the grown crystals to make radiation detectors. As the detector grade HPGe crystals, they have to meet two critical requirements: an impurity level of ∼10 9 to 10 atoms /cm 3 and a dislocation density in the range of ∼10 2 to 10 4 / cm 3 . In the present work, we have used the following four characterization techniques to investigate the properties of the grown crystals. First of all, an x-ray diffraction method was used to determine crystal orientation. Secondly, the van der Pauw Hall effect measurement was used to measure the electrical properties. Thirdly, a photo-thermal ionization spectroscopy (PTIS) was used to identify what the impurity atoms are in the crystal. Lastly, an optical microscope observation was used to measure dislocation density in the crystal. All of these characterization techniques have provided great helps to our crystal activities.